2011
DOI: 10.1002/elps.201100227
|View full text |Cite
|
Sign up to set email alerts
|

On chip electrofusion of single human B cells and mouse myeloma cells for efficient hybridoma generation

Abstract: This article describes the development and full characterization of a microfluidic chip for electrofusion of human peripheral blood B-cells and mouse myeloma (NS-1) cells to generate hybridomas. The chip consists of an array of 783 traps, with dimensions that were optimized to obtain a final cell pairing efficiency of 33±6%. B cells were stained with a cytoplasmic stain CFDA to assess the different stages of cell fusion, i.e. dye transfer to NS-1 cells (initiating fusion) and membrane reorganization (advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The first group of such systems utilize high-density hydrodynamic cell trap arrays within flowthrough channels [28][29][30][31]32 ] (Figure 1d). In particular, we developed a method, termed 'microfluidic cell pairing' [29,31,32 ], that uses microfabricated capture-cups to properly isolate and pair thousands of cells in parallel using a multistep cell loading procedure.…”
Section: Defining Intercellular Interactionsmentioning
confidence: 99%
“…The first group of such systems utilize high-density hydrodynamic cell trap arrays within flowthrough channels [28][29][30][31]32 ] (Figure 1d). In particular, we developed a method, termed 'microfluidic cell pairing' [29,31,32 ], that uses microfabricated capture-cups to properly isolate and pair thousands of cells in parallel using a multistep cell loading procedure.…”
Section: Defining Intercellular Interactionsmentioning
confidence: 99%
“…After counting on average 500 droplets per experiment (n = 5), of which 15% (75 droplets) contained two cells and qualified for possible electrofusion, 19 successful electrofusion events were found resulting in 5 % electrofusion efficiency. The established efficiency is comparable to the efficiency of both commercially available methods [53][54][55] as well as on-chip methods 52,[56][57][58] . To compete with existing methods, the electrofusion efficiency must be further improved, and there are several realistic opportunities for this.…”
Section: Resultsmentioning
confidence: 79%
“…The electrode width can also be adjusted, but should not be more than the droplet length, as the droplet must be in contact with both electrodes to create the electric field over the encapsulated cells. Additionally, previous results showed that applying multiple pulses (hence employing multiple electrode pairs) resulted in higher fusion efficiencies 52 .…”
Section: Discussion Of the Experimental Procedures And Setupmentioning
confidence: 97%
See 2 more Smart Citations